Application Of The Green Building Concept In Children's Libraries (International Journal of Architecture and Urbanism, 2024)
There is a low rate of literacy in Indonesian society. The poor interest in reading among Indonesians makes this worse. One of the key facilities for enhancing the caliber of human resources is the library. A venue for the dissemination of knowledge is the library. Global developments are significantly influenced by fast-evolving knowledge and technology. As much as 70% of Indonesian pupils, according to a 2018 assessment by the Program for International Pupils Assessment (PISA), have poor reading skills and are unable to identify the main idea of a brief paragraph. With these circumstances, Indonesian libraries are unable to sustain the country's population's desire in reading. To develop reading skills from an early age, this paper will undertake green building research in kid-friendly apartment complexes and libraries and investigate design approaches that utilize these concepts to boost user comfort and productivity. The process involves examining library resources found in both online and print scientific journals. This research develops a green building design concept with several applications, such as integrating green open space on the building site into a central green open space in an exemplary garden, integrating each floor of the building into green open space, maximizing daylight for building lighting during the day, using solar panels to store energy from sunlight, and using filtered rinse water to water plants.Keywords: children's library, green building, literacy